A New Metric of Market Underreaction to Earnings Announcements: An Empirical Test. (7th August 2020) - Chung, Kee H.; Kim, Oliver; Lim, Steve C.; Yang, Sean
Abstract: This paper provides empirical evidence that the squared correlation coefficient between order imbalance and earnings surprise (COE) measures market underreaction and predicts the post‐earnings announcement drift. We find strong evidence that COE during the announcement period predicts price movements (returns) during the post‐announcement period in the expected direction. We find qualitatively similar results using risk‐adjusted returns (i.e., Fama‐French, Carhart, and Pastor‐Stambaugh factor alphas), suggesting that well‐known risk factors do not explain the profitability of trading strategy based on COE.